Monoicado: Monopoly game modification for science learning on Light and Optical Instruments - Damayanti, Ayu Try; Fajar, Dinar Maftukh; Habibbulloh, Muhammad (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
Monoicado (The Science Monopoly Game on Light and Optical Instruments) is an educational game based on a monopoly game developed with the aim of helping students understand the material, encouraging students to be more active, and providing a fun atmosphere in learning science subjects on the material of Light and Optical Instruments at the junior high school level. This paper aims to describe (1) the feasibility and (2) students' responses to the results of the media development. This study implemented the 4D research and development model proposed by Thiagarajan (define, design, develop, and disseminate) where the dissemination stage was not carried out. The research subjects involved 2 material experts, 2 media experts, 2 teachers as users, and 33 students from one junior high school in Bondowoso district, East Java. The data obtained were analyzed quantitatively and qualitatively . Quantitative analysis was carried out on the acquisition of validation scores given by experts, users, and students. Qualitative analysis was conducted on all responses to the media. The media developed is considered very valid in all three aspects of assessment (material, media, and practicality). Students' responses to the media are visualized in a wordcloud with the most comments: easy to understand, fun, and to train memory on the Light and Optical Instruments material.